From Bilingualism to Code Mixing and Code Switching Uttered by Indonesian Youth - Dewirahmadanirwati Dewirahmadanirwati; Mac Aditiawarman (Fakultas Sastra Universitas Ekasakti, 2023)
Indonesian people tend to use code-mixing or code-switching in every language activity. Language/Code or is a way that is used to express something. For people who are used to being bilingual/multilingual, it will be seen how they speak. The way they speak sounds sometimes their speech is mixed with foreign languages. This language mixing is known as code mixing. Code mixing occurs when someone who is fluent in both languages ​​uses elements of the two languages ​​intentionally and simultaneously incorporates elements of one language into another in one utterance. In addition, code switching also occurs when someone uses language elements in the form of sentences or clauses to exchange with other language elements in different languages. Such symptoms are often carried out by educated people, public figures, politicians, and government officials. The subject of this research is the conversation between Maudy Ayunda and Robert in an interview at Perspektif Metro TV on Monday, December 30, 2019. There are the research questions in this research, first to find the types of code-mixing and code-switching, second, the reasons for code-mixing/code-switching, and the last, to indicate the matrix language in the interview. To answer the research questions, the researcherss applied sociolinguistic theory, especially the theories on types and reasons of code-mixing and code-switching proposed by Hoffman (1991) and how many codes in their uttarences based on Myers-Scotton theory (2006). This research using a qualitative approach and observation method from Sudaryanto (2015) which is an uninvolved interview observation technique. In this technique, the researcherss does not get involved directly in the dialogue in the interview between Maudy Ayunda and Robert. Then, the researcherss uses the note-taking, of the uttarences that is produced by Maudy and Robert in the interview. Then, the researcherss classified those code-mixing and code-switching in a table to find the type of code-mixing and code-switching. After analyzing the data, there are 139 cases of code-mixing and 72 cases of code-switching. For the types of code-mixing, there is 108 intra-sentential, 28 intra-lexical and 3 involving a change in pronunciation. For types of code-switching, there is 68 inter-sentential, and 4 establishing with the previous speaker. For the reasons of code-mixing/code-switching, the researcherss found 31 data of talking about a particular topic, 1 data of quoting somebody else, 3 being emphatic about something, 6 of repetition used for classification and 1 of clarifying the speech content for the interlocutor. For the matrix in code-mixing, Indonesian 82% as matrix language and English 18% as an embedded language, and in code-switching, Indonesian 54% as matrix language and English 46%as an embedded language.